Increased salivary immunoglobulin A and reduced alpha-amylase activity in whole saliva from spastic cerebral palsy individuals - Leite, Mariana F.; Alves Aznar, Lauren Cardoso; Ferreira, Maria Cristina D. [UNESP]; Guare, Renata O.; Santos, Maria Teresa B. (Wiley-Blackwell, 2013)
BACKGROUND: Salivary immunoglobulin A (SIgA) together with innate defenses such as alpha-amylase, provides the 'first line of defense' against pathogens present at mucosal surfaces. This study aimed to evaluate salivary alpha-amylase and immunoglobulin A (IgA) in whole saliva of spastic cerebral palsy (CP) individuals.METHODS: Whole saliva was collected from 22 CP and 24 sibling volunteers with no neurological damage control groups (CG) (aged 7-14 years). The salivary flow rate, total protein and SIgA concentrations, and alpha-amylase activity were determined.RESULTS: The CP group presented higher salivary flow rate (35%) and lower total protein concentration (18%) compared with the CG (P <= 0.05). CPG had higher absolute (68%, mu g SIgA/ml) and relative (55%, mu g SIgA/mg prot and 108%, mu g SIgA/min) concentrations of IgA compared with the CG (P <= 0.05). CPG had lower relative alpha-amylase activity (15% mg malt/mg prot and 33%, mg malt/min) compared with the CG (P <= 0.05).CONCLUSION: This study concluded that CP individuals presented alterations in the profile of salivary proteins involved in the defense system of the oral cavity.
Keywords: salivary immunoglobulin A; alpha-amylase activity; cerebral palsy